The Urgency of Reformulating Election Dispute Resolution in Indonesia: A Comparative Study - Fauzan, Anis; Marsal, Irsyaf; Kaharuddin (Al-Risalah, 2026)
The Indonesian concept of the rule of law fundamentally adopts key elements of the Rechtstaat tradition, prioritizing the supremacy of law as the ultimate instrument in governing national life, where the protection of Human Rights is not merely a legalistic formality but the core spirit animating every regulation to ensure that popular sovereignty remains within the corridors of respect for human dignity. However, current realities demonstrate that the protection of the right to vote and be elected in Indonesia has undergone significant degradation due to legal uncertainty arising from the highly complex fragmentation of election dispute resolution bodies, involving at least five different institutions with frequently overlapping authorities, thereby creating a confusing judicial bureaucratic labyrinth. This study employs a normative legal research method with statutory, comparative, and conceptual approaches through literature study techniques to analyze the problems of the electoral legal structure descriptively and prescriptively, integrating Lawrence M. Friedman’s legal system theory and Gustav Radbruch’s triad of legal goals to holistically examine the aspects of justice, certainty, and legal utility. The results reveal that the phenomenon of sectoral ego within Indonesia’s electoral law enforcement system reflects a democratic paradox where an excessively broad distribution of authority, lacking integrative hierarchical coordination, creates conflicting decisions and delegitimizes the integrity of general election results. As a strategic solution, this study recommends reformulating the dispute resolution model through the establishment of a tiered "one-door system" special electoral court under the auspices of the Supreme Court to guarantee the synchronization of rulings as well as procedural and substantive legal certainty without necessitating an amendment to the 1945 Constitution, provided that the Constitutional Court's authority to adjudicate result disputes remains constitutionally preserved.